FOREIGN INCOME – PROBLEMS OF DOUBLE TAXATION (International Journal of Innovative Technologies in Economy, 2018)
The article highlights implications of foreign income taxation of Ukrainian tax residents. Based on the effective Tax Conventions on Income and on Capital, individuals can claim a credit of tax paid abroad against their Ukrainian tax due. However, the claim must be supported by a specific document prescribed by Ukrainian legislation. In practice, the obtaining of the proper document from foreign tax authorities may be impossible for taxpayers, bringing the double taxation of personal income. Thus, the options of improvement of tax credit mechanism and unification of official confirmation of tax base and tax payment were proposed.